A concordância verbal na fala de Vitória - Benfica, Samine de Almeida (2016)
The central purpose of this research is to analyze the phenomenon verb agreement in first and third person plural in Portuguese spoken in Vitória - ES. Therefore, we will use the theoretical assumptions of Variationist Sociolinguistics (LABOV, 2008 [1972]), which is also a reference to numerous studies about the verbal agreement variable in several communities in Brazil and in the world. Linguists in this area believe that the language is heterogeneous and that there are factors of linguistic and social order acting on it, which makes it manifest so many variations. It is our interest to identify these factors and understand their systematization of this strongly stereotyped phenomenon. The development of this research, which has a quantitative and qualitative character, ocurred through the analysis of interviews, drawn from two samples of Portuguese spoken in Vitória: the first, a more careful speech, is the “Português falado na cidade de Vitória” (Portvix), comprising typically 46 labovian interviews (YACOVENCO, 2009; 2012); the second, in casual speech, composed of three recordings (CALMON, 2010). Our analyzes are more focused on the more careful speech. We treat separately the variable verbal agreement in first person plural and in third person plural, because we believe that these are two dependent variables with different properties, but also with a few similarities. For the statistical treatment of the data from our corpus, we use the Goldvarb X program (SANKOFF; TAGLIAMONTE; SMITH, 2005). Of a global total of 3616 verbal occurrences, 521 are in first person plural, with 90,4% of tokens with plural marking, and 3095 are in third person plural, with 78,8% of tokens with plural marking. In general, our analysis reinforces the idea that the third person plural and first person plural are different dependent variables, which is justified, mainly, for three reasons: incidence rate in speech, overall agreement and social significance of each. Still, in both variables, the results indicate a shift toward standard variant, with the highest incidence of agreement in the speech of younger and more educated.